The Gut Microbiome as a Predictor of low FODMAP Diet Efficacy in Functional Bowel Disorders - Chumpitazi, BP (Curr Opin Gastroenterol, 2020)
PURPOSE OF THE REVIEW: Fermentable oligosaccharides disaccharides monosaccharides and polyols (FODMAP) dietary restriction ameliorates irritable bowel syndrome (IBS) symptoms; however, not all IBS subjects respond. Given the gut microbiome’s role in carbohydrate fermentation, investigators have evaluated whether the gut microbiome may predict low FODMAP diet efficacy. RECENT FINDINGS: Gut microbiome fermentation, even to the same carbohydrate, is not uniform across all individuals with several factors (e.g., composition) playing a role. In both children and adults with IBS, studies are emerging suggesting the gut microbiome may predict low FODMAP diet efficacy. However, there is significant heterogeneity in the approaches (study population, microbiome assessment methods, statistical techniques, etc.) used amongst these studies. SUMMARY: The gut microbiome holds promise as a predictor of low FODMAP diet efficacy. However, further investigation using standardized approaches to evaluate the microbiome while concomitantly assessing other potential predictors are needed to more rigorously evaluate this area.